Odpowiedzi

  • emru
  • Początkujący
2010-01-21T17:41:39+01:00
A)3x+2y=13
2x+y=11\*(-2)
3x+2y=13
-4x-2y=-22
-x=-9
x=9
y=-7

b)5x+3y=0
-x-2y=7\*5
5x+3y=0
-5x-10y=35
-7y=35\/(-7)
y=-5
x=3

c)3u+2v=2\*(-2)
5u+4v=6
-6u-4v=-4
5u+4v=6
-u=2
u=-2
v=4

d)3s+5t=-6
1,5s-2t=-3\*(-2)
3s+5t=-6
-3s+4t=6
9t=0
t=0
s=-2

e)5=3x-y
5x-2y=7
3x-y=5\(*-2)
5x-2y=5
-6x+2y=-10
5x-2y=5
-x=-5
x=5
y=10

f)x-3y=5
y+3x=-5\*3
x-3y=5
3y+9x=-15
10x=-10
x=-1
y=-2
Najlepsza Odpowiedź!
2010-01-21T17:44:28+01:00
A)
{3x+2y=13
{2x+y=11 |*(-2)

{3x+2y=13
+{-4x-2y=-22
============
-x=-9
x=9

3*9+2y=13
2y=-14
y=-14/2

{x=9
{y=-14/2


b)
{5x+3y=0
{-x-2y=7 |*5

{5x+3y=0
{-5x-10y=35
===========
-7y=35
y=-5

5x+3*(-5)=0
5x=15
{x=3
{y=-5

c)
{3u+2v=2 |*(-2)
{5u+4v=6

{-6u-4v=-4
{5u+4v=6
==========
-u=2
u=-2

5*(-2)+4v=6
4v=16
{v=4
{u=-2

d)
{3s+5t=-6
{1,5s-2t=-3 |*(-2)

{3s+5t=-6
{-3s+4t=6
=========
9t=0
t=0

3s+5*0=-6
3s=-6
{s=-2
{t=0

e)
{3x-y=5 |*(-2)
{5x-2y=7

{-6x+2y=-10
{5x-2y=7
===========
-x=-3
x=3

5*3-2y=7
-2y=-8
{y=4
{x=3

f)
{x-3y=5
{3x+y=-5 |*3

{x-3y=5
{9x+3y=-15
============
10x=-10
x=-1
-1-3y=5
-3y=6
{y=-2
{x=-1